2019
DOI: 10.1590/1676-0611-bn-2018-0684
|View full text |Cite
|
Sign up to set email alerts
|

Marine ichthyofauna of Santa Catarina Island, Southern Brazil: checklist with comments on the species

Abstract: This study aimed to present a checklist of marine fishes from coastal environments of the Island of Santa Catarina, including comments on the zoogeographic affinities, conservation status of each species, and functional groups. A total of 169 fish species belonging to 30 orders and 58 families were recorded. The most speciose families were Sciaenidae, Carangidae and, Engraulidae, representing 26,62% of the recorded species. Anchoa was the richest genus, followed by Sphoeroides and Cynoscion. Most of the specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
1
0
8
Order By: Relevance
“…Sendo assim, as áreas portuárias são consideradas fontes de substâncias tóxicas, nas quais existem poluentes capazes de afetar negativamente os ecossistemas marinhos (SOUSA; ALMEIDA; CARVALHO-NETA, 2013). Os ambientes estuarinos possuem grande produtividade biológica, que é ameaçada por atividades antrópicas, como pesca predatória e atividades portuárias, o que pode acarretar à perda de habitat, introdução de espécies e poluição ambiental (RIBEIRO et al, 2019).…”
Section: Introductionunclassified
“…Sendo assim, as áreas portuárias são consideradas fontes de substâncias tóxicas, nas quais existem poluentes capazes de afetar negativamente os ecossistemas marinhos (SOUSA; ALMEIDA; CARVALHO-NETA, 2013). Os ambientes estuarinos possuem grande produtividade biológica, que é ameaçada por atividades antrópicas, como pesca predatória e atividades portuárias, o que pode acarretar à perda de habitat, introdução de espécies e poluição ambiental (RIBEIRO et al, 2019).…”
Section: Introductionunclassified
“…In this study, we found that the composition and structure of fish communities in general in the PEC and adjacent continental shelf follow a pattern observed in tropical western Atlantic estuaries (Blaber 1997(Blaber , 2002, with a predominance of species of the family Sciaenidae, which in this study represented more than 51% of all recorded families. For example, in a survey of the fish fauna on Santa Catarina Island in southern Brazil, of the 58 species recorded, 20 were classified as Sciaenidae (Ribeiro et al 2019). A pioneering survey (Vinson et al 2004) showed that because of the importance of the family Sciaenidae in that ecosystem (Barletta-Bergan et al 2002), it was necessary to deepen it using more refined techniques with phylogenetic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Os peixes capturados foram identificados ao menor nível taxonômico possível e categorizados em guildas de uso do estuário (uso do habitat) e guildas alimentares (dieta) (Figueiredo & Menezes, 1978Fischer, 1978;, 1985Guimarães, 1996;Elliott et al, 2007;Denadai et al, 2013;Silva-Junior;Carvalho & Vianna, 2013;Passos et al, 2013;Marceniuk et al, 2016;Marceniuk, 2018;Betancur-r et al, 2017;Froese & Pauly, 2019;Ribeiro et al, 2019;Eschmeyer, 2020).…”
Section: Coleta De Dadosunclassified